Influence of ambient humidity on the attachment ability of ladybird beetles (Coccinella septempunctata) - Heepe, Lars; Wolff, Jonas O.; Gorb, Stanislav N. (Beilstein Journal of Nanotechnology, 2016)
Many insects possess adhesive foot pads, which enable them to scale smooth vertical surfaces. The function of these organs may be highly affected by environmental conditions. Ladybird beetles (Coccinellidae) possess dense tarsal soles of tenent setae, supplemented with an adhesive fluid. We studied the attachment ability of the seven-spotted ladybird beetle (Coccinella septempunctata) at different humidities by horizontal traction experiments. We found that both low (15%) and high (99%) relative humidities lead to a decrease of attachment ability. The significantly highest attachment forces were revealed at 60% humidity. This relationship was found both in female and male beetles, despite of a deviating structure of adhesive setae and a significant difference in forces between sexes. These findings demonstrate that not only dry adhesive setae are affected by ambient humidity, but also setae that stick due to the capillarity of an oily secretion.
Keywords: adhesion; beetle; biomechanics; force measurement; friction; insect; locomotion; surface